A High-Fat Western Diet Attenuates Intestinal Changes in Mice with DSS-Induced Low-Grade Inflammation. Issue 3 (2nd December 2021) - Papoutsis, Dimitrios; Cardoso da Rocha, Sérgio Domingos; Herfindal, Anne Mari; Kjølsrud Bøhn, Siv; Carlsen, Harald
ABSTRACT: Background: A Western diet (WD) is associated with increased inflammation in the large intestine, which is often ascribed to the high dietary fat content. Intestinal inflammation in rodents can be induced by oral administration of dextran sodium sulfate (DSS). However, most studies investigating effects of WD and DSS have not used appropriate low-fat diets (LFDs) as control. Objectives: To compare the effects of a WD with those of an LFD on colon health in a DSS-induced low-grade colonic inflammation mouse model. Methods: Six-week-old male C57BL/6JRj mice were fed an LFD (fat = 10.3% energy, n = 24) or a WD (fat = 41.2% energy, n = 24) for 15 wk [Experiment 1 (Exp.1)]. Half the mice on each diet ( n = 12) then received 1% DSS in water for 6 d with the remainder ( n = 12 in each diet) administered water. Disease activity, proinflammatory genes, inflammatory biomarkers, and fecal microbiota (16S rRNA) were assessed (Exp.1). Follow-up experiments (Exp.2 and Exp.3) were performed to investigate whether fat source (milk or lard; Exp.2) affected outcomes and whether a shift from LFD to WD 1 d prior to 1% DSS exposure caused an immediate effect on DSS-induced inflammation (Exp.3). Results: In Exp.1, 1% DSS treatment significantly increased disease score in the LFD group compared with the WD group (2.7 compared with 0.8; P < 0.001). Higher concentrations of fecal lipocalin (11-fold; P < 0.001), proinflammatory gene expression (≤82-fold), and Proteobacteria were observed in LFD-fed mice compared with the WD group. The 2 fat sources in WDs (Exp.2) revealed the same low inflammation in WD+DSS mice compared with LFD+DSS mice. Finally, the switch from LFD to WD just before DSS exposure resulted in reduced colonic inflammation (Exp.3). Conclusions: Herein, WDs (with milk or lard) protected mice against DSS-induced colonic inflammation compared with LFD-fed mice. Whether fat intake induces protective mechanisms against DSS-mediated inflammation or inhibits establishment of the DSS-induced colitis model is unclear.